Host Co-Occurrence and Population Size Explain Genetic Differentiation and Diversity in Seal Lice - Sromek, Ludmila; Johnson, Kevin P.; Kunnasranta, Mervi; Rosing‐Asvid, Aqqalu; Bäcklin, Britt‐Marie; Tasmagambetova, Aselle; Tovassarov, Adylkhan; Rusinek, Olga; Ziel, Heather L.; Rubio‐García, Ana; Nyman, Tommi (Wiley-Blackwell, 2025)
We studied the drivers of population-genetic structuring and genetic diversity in specialist parasites based on whole-genome resequencing data from 82 Echinophthirius horridus seal louse individuals sampled from 12 ecologically and behaviourally different phocine seal species, subspecies and populations across the Holarctic. We found that the main genetic disjunctions in E. horridus lice occur across seal host species and subspecies, with a further level of population subdivision emerging among host individuals within some populations. Endemic and relict landlocked seal (sub)species host the genetically most distinct louse populations, while lice associated with sympatric marine seals show signatures of occasional gene flow across hosts. Within the latter, the most extreme case is seen in the near-panmictic lice associated with northern European grey and harbour seals, which aggregate in shared rookeries and colonies. Although the louse and seal phylogenies were overall statistically significantly congruent, evidence for similar host shifts in the past is reflected in several conflicts in the phylogenetic trees of the lice and their hosts. Population-level mean heterozygosity and theta in seal lice varied considerably, and both measures of genetic variation were statistically significantly related to host population size. Taken together, our results support a non-adaptive model of parasite diversification, in which geographic and behavioural isolation among hosts drives parasite genetic differentiation, and genetic erosion in bottlenecked hosts cascades up to their specialist parasites. Our results provide new insights into processes that generate parasite diversity and trigger parallel losses of genetic diversity in endangered host–parasite systems.
Keywords: coevolution; genetic diversity; host-associated genetic differentiation; host–parasite interactions; infrapopulation structure